Association Between Facility Type During Pediatric Inpatient Rehabilitation and Functional Outcomes - Fuentes, Molly M. (Arch Phys Med Rehabil, 2016)
OBJECTIVE: To compare functional outcomes between children receiving inpatient rehabilitation at children’s hospitals and those at other facilities. DESIGN: Retrospective cohort study. SETTING: Inpatient rehabilitation facilities. PARTICIPANTS: Children (N=28,793) aged 6 months to 18 years who received initial inpatient rehabilitation. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Total, cognitive, and motor developmental functional quotients (DFQs; which is the WeeFIM score divided by age-adjusted norms and multiplied by 100) at discharge from inpatient rehabilitation and WeeFIM efficiency (the change in WeeFIM score from admission to discharge divided by the length of the rehabilitation stay), adjusting for age, sex, race, insurance, region, admission function, impairment type, discharge year, and length of stay. RESULTS: A total of 12,732 children received rehabilitation at 25 children’s hospitals and 16,061 at 36 other facilities (general hospitals or freestanding rehabilitation hospitals). Adjusting for clustering by facility, patients at children’s hospitals had a lower cognitive DFQ at admission (difference between children’s hospitals and other facility types, −3.8; 95% confidence interval [CI], −7.7 to −0.1), a shorter length of stay (median, 16d vs 22d; P<.001), and a higher WeeFIM efficiency (difference, 0.63; 95% CI, 0.25–1.00) than did children at other facility types. Rehabilitation in a children’s hospital was independently associated with a higher discharge cognitive DFQ (regression coefficient, 2.3; 95% CI, 0.3–4.2) and more efficient rehabilitation admissions (regression coefficient, 0.3; 95% CI, 0.1–0.6). CONCLUSIONS: Children who receive inpatient rehabilitation at children’s hospitals have more efficient inpatient rehabilitation admissions, a shorter median length of stay, and a slight improvement in cognitive function than do children at other facility types.